2020
DOI: 10.1038/s41598-020-68752-2
|View full text |Cite
|
Sign up to set email alerts
|

RT-qPCR analyses on the osteogenic differentiation from human iPS cells: an investigation of reference genes

Abstract: Reverse transcription quantitative PCR (RT-qPCR) is used to quantify gene expression and require standardization with reference genes. We sought to identify the reference genes best suited for experiments that induce osteogenic differentiation from human induced pluripotent stem cells. They were cultured in an undifferentiated maintenance medium and after confluence, further cultured in an osteogenic differentiation medium for 28 days. RT-qPCR was performed on undifferentiation markers, osteoblast and osteocyt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 32 publications
2
21
0
Order By: Relevance
“…Phosphoglycerate kinase 1 (PGK1) and Glyceraldehyde-3-phosphate dehydrogenase (GAPDH) are glycolytic enzyme involved in several metabolic pathways that are essential for cell growth and proliferation. The expression of these genes has been shown to differ in different tissue types and environment conditions 54 , 55 because of its functions in transcriptional and posttranscriptional gene regulation, intracellular membrane trafficking, DNA replication and reparation 56 , 57 .…”
Section: Resultsmentioning
confidence: 99%
“…Phosphoglycerate kinase 1 (PGK1) and Glyceraldehyde-3-phosphate dehydrogenase (GAPDH) are glycolytic enzyme involved in several metabolic pathways that are essential for cell growth and proliferation. The expression of these genes has been shown to differ in different tissue types and environment conditions 54 , 55 because of its functions in transcriptional and posttranscriptional gene regulation, intracellular membrane trafficking, DNA replication and reparation 56 , 57 .…”
Section: Resultsmentioning
confidence: 99%
“…The specimens were subjected to PBS washing three times after culturing the specimens for 14 days, and then they were put off in cold TRIzol Reagent (1 ml). The total RNA of each sample was extracted and again put off in RNase-free water (50 μL) using the standard TRIzol protocol (Okamura et al, 2020). Following the protocol, the cDNA was created and stored at -20 °C until further analysis.…”
Section: Osteogenic Differentiation By Gene Expression Studiesmentioning
confidence: 99%
“…Additionally, various methodology articles have made further efforts to ensure the stability and optimal quantity of reference genes to obtain accurately reproducible data, providing considerable impetus towards perfecting RT-qPCR [19][20][21][22]. Subsequent bone and cartilage bioengineering studies have suggested that the stability and normalization quantity of reference genes should not only be determined by cell or tissue type but should also be re-optimized for experiments under different processing conditions [23,24], which has provided an extra step in perfecting the understanding of the MIQE guidelines.…”
Section: Introductionmentioning
confidence: 99%